1984
DOI: 10.1172/jci111200
|View full text |Cite
|
Sign up to set email alerts
|

A luteinizing hormone-releasing hormone agonist decreases biological activity and modifies chromatographic behavior of luteinizing hormone in man.

Abstract: Astract. The effect ofthe luteinizing hormonereleasing hormone (LHRH) agonist, NEth]LHRH (LHRHA), on luteinizing hormone (LH) bioactivity was assessed with a rat interstitial cell assay in four men during a 14-d treatment period. Biologic/ immunologic (B/I) ratios were unchanged initially with treatment but by day 12 had fallen to levels lower than basal values. Frequent sampling on day 12 revealed blunted gonadotropin responsiveness to LHRHA and absence of spontaneous LH pulsations. Despite continued admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
1
1

Year Published

1984
1984
1991
1991

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(23 citation statements)
references
References 13 publications
3
18
1
1
Order By: Relevance
“…Our clinical results also attest to the high efficacy of microcapsules (11). In addition, the immunoreactive LH produced after chronic stimulation with LH-RH agonists was reported to have decreased biological activity (18,19).…”
supporting
confidence: 73%
See 1 more Smart Citation
“…Our clinical results also attest to the high efficacy of microcapsules (11). In addition, the immunoreactive LH produced after chronic stimulation with LH-RH agonists was reported to have decreased biological activity (18,19).…”
supporting
confidence: 73%
“…In any case, ovarian suppression after chronic [D-Trp6]LH-RH administration may occur in the presence of high immunoreactive serum LH levels (18,19). However, the antitumoral activity of [D-Trp6]LH-RH could be related in part to a direct action on this agonist on the pituitary tumor cells.…”
mentioning
confidence: 99%
“…In adults, such a condition (e.g. after long term treatment with GnRH agonist) is related to decreased B/I ratio of circulating LH (27)(28)(29). Inasmuch as the acute GnRH stimulation was able to increase the B/I ratio only in CD, this response may require priming of the pituitary by previous GnRH pulses.…”
Section: Discussionmentioning
confidence: 99%
“…These re sults as well as clinical evidence indicate that sustained treatment with GnRH ago nists most likely abolishes pituitary func tion, in spite of the fact that gonadotropin radioimmunoassays based on polyclonal an tibodies do not show this effect. This hy pothesis is sustained by the work of Evans et al [10], who showed that GnRH agonists markedly decrease bioactive LH but at the same time induce the appearance of slowmigrating immunoreactive LH on Sephadex columns.…”
Section: Introductionmentioning
confidence: 88%